(3HjhJ dG JONdgG GdedGFcI (B/s - (3GHf eMeO, EHQGgjes ((3WfWG (B- (3eUQ (B:s (3OGQ GdUMGHI ddJQGK,s, 1990)
(3jJfGhd cJGH (B((3HjhJ dG JONdgG GdedGFcI(B) (3hGdPj bGe HJCdjag CHh MPjaI EHQGgje Hf eMeO, ehVhY (B((3HjhJ dG JONdgG GdedGFcI(B) (3gPG GdcJGH HMK Yf GdHjhJ GdJj dG JONdgG GdedGFcI, MjK jTJcj cKjQG ef GdfGS ef bdI GdHQcI, hYOe GSJbQGQ GdfaS, hef JZdH GdeGOjGJ Ydi MjGJfG GdOfjG(B. (3hHOQGSI gPG GdCeQ hLO Cf SHH Pdc gh(B: (3GdHYO Yf Gddg, hgLQ GdedGFcI dHjhJfG, hMdhd GdTjGWjf HOdG efgG(B. (3hGdcJGH jhVM dfG HGdJaUjd eGgjI GdedGFcI haVdgG Ydi GdHjJ GdeSde, hGdHjhJ GdJj dG JONdgG GdedGFcI hCSHGH YOe ONhdgG dgPg GdHjhJ, eSJYjfG HGdSfI GdfHhjI hGdCMGOjK GdUMjMI aj gPG GdCeQ(B. s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdOYhI GdESdGejIs; (3GdhYX hGdEQTGOs